A comprehensive examination of the memory profile of youth with Down syndrome in comparison to typically developing peers. Issue 6 (17th August 2020) - Godfrey, Mary; Lee, Nancy Raitano
ABSTRACT: Down syndrome (DS) is associated with significant memory deficits beyond overall global cognitive impairment. Although a number of studies have examined memory abilities in adults and teens with DS, very few studies have examined memory abilities in children with DS. Additionally, research has yet to examine prospective memory (i.e., remembering to carry out an action in the future) in youth with DS. Consequently, the current study aimed to comprehensively examine the memory profile, including learning, immediate recall, delayed recall and prospective memory, of youth with DS ( n = 22, age M = 11.43) in comparison to typically developing, mental-age (MA) matched children ( n = 20, age M = 5.04) Consistent with past research, the results indicated that youth with DS performed significantly below MA-expectations on tasks of immediate verbal recall, learning across trials, and prospective memory, and there was a trend toward youth with DS performing below MA-expectations on delayed recall tasks. However, youth with DS did not differ significantly from MA-matched peers on immediate visual recall, rate of learning across trials, or proportion of items recalled on verbal and visual memory tasks following a delay (i.e., proportion relative to their own recall performance prior to the delay). These results highlight the relative strengths and challenges experienced by youth with DS on different learning and memory tasks. The implications of these findings for educators and caregivers are discussed.